Modern weapons and military equipment for issue 1/2013 - Gaćeša, Nebojša Nikola; Ostojić, Nikola M.; Vučković, Dragan (Vojnotehnički glasnik / Military Technical Courier, 2013)
The new phase of development of intelligence technology - Paradigm Management System battlefield; British police tested the laser gun to blinding protesters; FLIR thermal imaging cameras at the fair ISEC; Russian GLONASS global positioning system now covers the entire planet; Dassault delivered the first Rafal equipped with AESA system; France develops air defense Submarines; GD is a modification of the engine to the tank 1 and M caterpillar Stryker; GD is a modification of the engine to the tank 1 and M caterpillar Stryker; Indian defense industry is preparing for hypersonic test; India will soon begin testing a self-propelled cannon Catapult Mk II; Iran shows the latest armored vehicles; Northrop Grumman ending improvement of radar at all bombers B-2; Norwegian Navy fired its first NSM; New details on the supply of armored personnel carriers for the Marines; New package for modernization of T 72M1; Ukrainian companies join forces to develop seeker missile R-2713th; Russia: Successful testing intercontinental and cruise missiles; Other invisible Chinese plane; Future Weapons: Missile microwave which "burns" computers and harmless to humans.